Effects of partial sleep deprivation on slow waves during non-rapid eye movement sleep: A high density EEG investigation. Issue 2 (February 2016) - Plante, David T.; Goldstein, Michael R.; Cook, Jesse D.; Smith, Richard; Riedner, Brady A.; Rumble, Meredith E.; Jelenchick, Lauren; Roth, Andrea; Tononi, Giulio; Benca, Ruth M.; Peterson, Michael J.
Highlights: It is not clear whether homeostatic regulation of slow waves occurs over repeated nights of partial sleep restriction. High-density EEG sleep recordings demonstrate dynamic changes during partial sleep deprivation and recovery that vary depending on cortical topography. These results confirm a homeostatic response to partial sleep loss in humans. Abstract: Objective: Changes in slow waves during non-rapid eye movement (NREM) sleep in response to acute total sleep deprivation are well-established measures of sleep homeostasis. This investigation utilized high-density electroencephalography (hdEEG) to examine topographic changes in slow waves during repeated partial sleep deprivation. Methods: Twenty-four participants underwent a 6-day sleep restriction protocol. Spectral and period-amplitude analyses of sleep hdEEG data were used to examine changes in slow wave energy, count, amplitude, and slope relative to baseline. Results: Changes in slow wave energy were dependent on the quantity of NREM sleep utilized for analysis, with widespread increases during sleep restriction and recovery when comparing data from the first portion of the sleep period, but restricted to recovery sleep if the entire sleep episode was considered. Period-amplitude analysis was less dependent on the quantity of NREM sleep utilized, and demonstrated topographic changes in the count, amplitude, and distribution of slow waves, with frontal increases in slow wave amplitude, numbers of high-amplitude waves, and amplitude/slopes of low amplitude waves resulting from partial sleep deprivation. Conclusions: Topographic changes in slow waves occur across the course of partial sleep restriction and recovery. Significance: These results demonstrate a homeostatic response to partial sleep loss in humans.